WHEN VALVE LEAKS AND BLOOD BREAKS: PARAVALVULAR LEAK-INDUCED HEMOLYTIC ANEMIA IN YOUNG PATIENT WITH MECHANICAL AORTIC VALVE AND MITRAL ANNULOPLASTY - Meliana, Astri; Putri, Luh Putu Previyanti Dharma (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2026)
Paravalvular leak (PVL) is a significant complication following valve surgery, typically affecting elderly patients and manifesting as heart failure or hemolytic anemia. While uncommon in younger populations, its occurrence presents unique clinical challenges. This report describes a unique case of a 19-year-old male presenting with a rare combination of aortic paravalvular leakage and mitral annuloplasty ring dehiscence. Five months post-surgery, the patient presented with icteric sclerae and tea-colored urine. Laboratory evaluation confirmed intravascular mechanical hemolysis, evidenced by indirect hyperbilirubinemia and the hallmark presence of schistocytes (helmet cells) on a peripheral blood smear. Transthoracic echocardiography identified the specific mechanical triggers: a prosthetic aortic valve PVL and severe mitral regurgitation due to ring dehiscence. Management involved immediate medical stabilization using diuretics, rate-control agents, and the continuation of lifelong warfarin therapy. Due to the mechanical nature of the defect, the patient was referred to a tertiary center for transesophageal echocardiography and evaluation by a multidisciplinary heart team for definitive surgical or transcatheter intervention. This case emphasizes the critical importance of early clinical recognition of mechanical hemolysis in rare, young populations with complex prosthetic valve failures. A multidisciplinary heart team approach and gold-standard imaging are essential to minimize morbidity and ensure the near-complete elimination of the leak required to resolve hemolysis.